AKSI SOBAT TB DALAM UPAYA MENGUBAH STIGMA UNTUK MENINGKATKAN PARTISIPASI MASYARAKAT MELAKUKAN PENJARINGAN PENYAKIT TUBERKULOSIS : The TB Friends Action Approach: Community-Based Education to Enhance Participation and Early Detection of Tuberculosis - Fea Firdani; Ariska Silviana; Aurelia Mayori; Azizah Salsabil Burhan; Dinda Modisa; Maya Selly Novikha; Meyrisma Yulianti; Nada Rudiaputri; Rahmi Syahriza; Zahra Putri Asri (BULETIN ILMIAH NAGARI MEMBANGUN, 2026)
Tuberculosis (TB) remains a major infectious disease in Indonesia. Data from the Ampalu Community Health Center in 2023 showed 93.5% service coverage for suspected TB patients (430 people), with 26 confirmed cases. However, from January to August 2024, only 33.3% of the screening target (66.7%) was achieved, revealing a gap in early detection and the need to enhance community participation. The TB Friend Action program was developed as a community-based intervention integrating education, case screening, and health information dissemination to improve knowledge, reduce stigma, and strengthen community involvement in TB control. The activity was implemented in September 2024 in Korong Palak Juha, Ampalu District, Padang Pariaman Regency, involving 48 participants from local communities and at-risk families, supported by cadres, community leaders, and community health center staff. The intervention comprised three components: interactive outreach using lectures and the Emo-demo method, sputum collection for case screening, and the distribution of educational media (leaflets, posters, banners, and x-banners). Evaluation through pre- and post-tests, observation, and screening analysis showed a significant improvement in knowledge, with the Wilcoxon Signed Rank Test yielding Z = -5.98 and p < 0.001 (pre-test 57.52 ± 14.57; post-test 68.10 ± 9.21). High community engagement was evident from active participation and the collection of 26 sputum samples for laboratory testing. The TB Friend Action effectively enhanced community understanding, reduced stigma, and fostered collaboration between communities and health workers. Integration with routine health center programs and regional policy support is recommended to ensure sustainable TB prevention and control.